The Teacher's Invisible Hand: A Meta-Analysis of the Relevance of Teacher–Student Relationship Quality for Peer Relationships and the Contribution of Student Behavior. (June 2022) - Endedijk, Hinke M.; Breeman, Linda D.; van Lissa, Caspar J.; Hendrickx, Marloes M. H. G.; den Boer, Larissa; Mainhard, Tim
The relationships that students have with teachers and peers are important for their academic, social, and behavioral development. How teachers relate to students may affect students' peer relationships and thereby foster or hamper students' development. To shed more light on the teacher's role with respect to peer relationships, this meta-analysis assessed the association between the quality of teacher–student and peer relationships (n = 297 studies; n = 1, 475 unique effect sizes). We took student behavior into account, as it is known to affect both types of relationship. In addition, design characteristics such as positive versus negative aspects of relationships, type of informants, and educational level were considered. Results showed that negative aspects of the teacher–student relationship in particular were predictive of peer relationships. Moreover, teacher–student relationship quality partially mediated the association between student behavior and peer relationships. For teachers, preventing or reducing negative aspects in their relationships with students who have behavioral problems can positively affect classroom peer relationships.